Line Balancing Analysis Using Ranked Positional Weight and Region Approach Method in Nail Production - Aji, Rindra Samawa; Widjajati, Endang Pudji (Journal La Multiapp, 2024)
At the moment industrial development, there is open competition on a national and international scale, the manufacturing and service industry sectors are developing very quickly. To create good, quality products and efficiency, the company must have a good track balance. As is the case in nail production. CV. XYZ is a company engaged in manufacturing. This company is located in the city of Sidoarjo, East Java. The aim of this research is to improve the balance of the work station trajectory of the nail production process at CV. XYZ. The method used in this research is the Region Approach and ranked positional weight. The best method chosen for this problem is the Region Approach method, because this method has the greatest line efficiency (68.17%), the smallest balance delay (31.83%), and the smallest smoothes index (100.63), so this method was chosen as the best method and can improve line balancing conditions in the company. The increase in line efficiency from 54.68% using the company method to 68.17% using the Region Approach method can occur due to a reduction in the number of work stations from 5 work stations as well as a decrease in the number of smoothing indexes from 168.20 to 100.63. which indicates that there is an increase in balance between work stations.